Transforming TVET: The Impact of Staff Training on Digitization Success - Zulkifli, Nurul Aida Syahirah; Bunawan, Ap-azli; Idris, Ahmad Sufi Alawi; Priyanto, Ida Fajar (Journal of Technical Education and Training, 2025)
In today’s fast-paced technological era, digitizing records has become a crucial step for organizations to improve efficiency, streamline data access, and ensure information security. As digitization continues to advance, incorporating digital tools and technologies into TVET (Technical and Vocational Education and Training) programs has become increasingly vital. Digitization improves the accessibility, delivery, and relevance of education and training, enabling learners to acquire skills that are crucial in an ever-changing job market. On top of that, TVET (Technical and Vocational Education and Training) is crucial for driving economic growth and decreasing unemployment by equipping individuals with the practical skills and knowledge required across various industries. It helps connect education with employment, ensuring that learners gain competencies that meet the needs of the job market. Despite the tremendous benefits of digitization, many organizations struggle with its implementation due to a lack of adequate training for their staff. Without the proper skills and knowledge, employees find it challenging to adapt to new systems, ultimately delaying or hindering the effectiveness of the digitization process. The absence of structured and continuous training not only slows down the transition but also poses risks such as data errors, information leakage, and decreased productivity. Besides, with the rapid advancement of technology, organizations are increasingly turning to digitization to enhance efficiency and streamline their record-keeping systems. This article will explore how the lack of staff training impacts the success of record digitization and suggest strategies to overcome these challenges.